The Challenges and Opportunities Associated with Biofortification of Pearl Millet (Pennisetum glaucum) with Elevated Levels of Grain Iron and Zinc - Manwaring, Hanna R.; Bligh, H. F. J.; Yadav, Rattan (Frontiers in Plant Science, 2016)
Deficiencies of essential micronutrients such as iron and zinc are the cause of extensive health problems in developing countries. They adversely affect performance, productivity and are a major hindrance to economic development. Since many people who suffer from micronutrient deficiencies are dependent on staple crops to meet their dietary requirements, the development of crop cultivars with increased levels of micronutrients in their edible parts is becoming increasingly recognised as a sustainable solution. This is largely facilitated by genetics and genomic platforms. The cereal crop pearl millet (Pennisetum glaucum), is an excellent candidate for genetic improvement due to its ability to thrive in dry, semi-arid regions, where farming conditions are often unfavourable. Not only does pearl millet grow in areas where other crops such as maize and wheat do not survive, it contains naturally high levels of micronutrients, proteins and a myriad of other health benefitting characteristics. This review discusses the current status of iron and zinc deficiencies and reasons why interventions such as fortification, supplementation and soil management are neither practicable nor affordable in poverty stricken areas. We argue that the most cost effective, sustainable intervention strategy is to biofortify pearl millet with enhanced levels of bioavailable iron and zinc. We discuss how naturally occurring genetic variations present in germplasm collections can be incorporated into elite, micronutrient rich varieties and what platforms are available to drive this research. We also consider the logistics of transgenic methods that could facilitate the improvement of the pearl millet gene pool.